(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Health is the most valuable asset in life, serving as the primary foundation for all human activities. The main focus of this research is to analyze the trend changes in the sales of Fituno from 2019 to 2022, taking into account the influence of brand image, product quality, promotion, and physical evidence factors. The study will delve into the motivations behind purchasing decisions and identify obstacles faced by consumers in making those decisions. Data collection for this research will span one month (between November-December 2023), with a random sampling process. The population for this study consists of all customers who purchased products at Apotek Kimia Farma SAMRAT from December 2023 to January 2024, with the population size unknown. The sample for this study includes customers of Apotek Kimia Farma SAMRAT who purchased Fituno products from November to December 2023, with the stipulation that the sample size is greater than or equal to 30 respondents and less than or equal to 500 respondents, or 30≥n ≤500. The analysis methods used include validity testing, reliability testing, classical assumptions, hypothesis testing, and multiple linear regression analysis using SPSS version 25. Based on the test results, it can be concluded that the brand image variable (X1) and physical evidence (X4 ) partially significantly influence the purchasing decision of Fituno products at Apotek Kimia Farma SAMRAT. However, the variables of product quality (X2) and promotion (X3), partially do not significantly influence the purchasing decision of Fituno products at Apotek Kimia Farma SAMRAT. Simultaneously, the variables of brand image (X1), product quality (X2), promotion (X3), and physical evidence factors (X4) significantly influence the purchasing decision of Fituno products at Apotek Kimia Farma SAMRAT.